Thrombus entrapped in patent foramen ovale: a rare form of thrombus in transit - Hooman Bakhshi; Zahra Meyghani; Zaid Shakir; Alexander Chen; Dawn Kershner (Journal of Community Hospital Internal Medicine Perspectives, 2015)
In rare cases, thrombus in transit can be entrapped in a patent foramen ovale (PFO). A patient with this condition is at high risk of embolic stroke and death. Early diagnosis and treatment is essential to help prevent stroke and death in these cases. There is no universal management guideline for this rare condition. The decision between medical versus surgical treatment should be made individually for each patient. We present a case of thrombus in transit entrapped in a PFO that was treated medically by lifelong anticoagulation.